In Botanical Gardens, Port of Spain, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
The postcard shows palms in the Botanical Gardens, Trinidad.
Colour: Sepia (print); Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Palms--Trinidad and Tobago; Plants--Trinidad and Tobago